2000
DOI: 10.1002/1097-0231(20000915)14:17<1625::aid-rcm72>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Positive ion electrospray ionization tandem mass spectrometry coupled to ion-pairing high-performance liquid chromatography with a phosphate buffer for the quantitative analysis of intracellular nucleotides

Abstract: A novel analytical procedure has been developed for the analysis of intracellular nucleotide triphosphates. Positive ion electrospray ionization tandem mass spectrometry (MS/MS) was interfaced to ion‐pairing high‐performance liquid chromatography (HPLC) utilizing a mobile phase containing 10 mM ammonium phosphate, pH 6.4, with 2 mM tetrabutylammonium hydroxide and 15% acetonitrile. The methodology was developed to support the analysis of the 5′‐triphosphate anabolite of the antiviral agent (−)‐FTC ((2R,5S)‐5‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 22 publications
1
54
0
Order By: Relevance
“…However, it normally requires complex sample clean-up procedures that are not desirable for higher throughput assays. Ion-pairing chromatography has been widely used as an alternative way for obtaining satisfactory retention of polar analytes [20][21][22][23][24][25][26]. The ion-pairing reagents added into mobile phase are used to improve chromatographic retention of analytes on the lipophilic stationary phase through the formation of neutral ion pairs.…”
Section: Development Of the Mixed-mode Hplc-ms/ms Methodsmentioning
confidence: 99%
“…However, it normally requires complex sample clean-up procedures that are not desirable for higher throughput assays. Ion-pairing chromatography has been widely used as an alternative way for obtaining satisfactory retention of polar analytes [20][21][22][23][24][25][26]. The ion-pairing reagents added into mobile phase are used to improve chromatographic retention of analytes on the lipophilic stationary phase through the formation of neutral ion pairs.…”
Section: Development Of the Mixed-mode Hplc-ms/ms Methodsmentioning
confidence: 99%
“…The nucleotides were separated by an ion-pairing reversed-phase high-performance liquid chromatography (HPLC) method adapted from a previously described method (8), using an XTerra MS C 18 column (100 mm ϫ 1 mm) equipped with a guard column (10 mm ϫ 2.1 mm) (both from Waters, Milford, MA). The standard solution and sample injection volume was 10 l; all standard solutions and samples were mixed 24:1 with a 2 M solution of the ion-pairing reagent tetrabutylammoniumacetate (Sigma-Aldrich, Steinheim, Germany) to obtain a final tetrabutylammoniumacetate concentration of 80 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Methods using positive-ion ESI-MS have shown their fast, specific, and sensitive advantages. Claire [23] reported the detection of a unique and abundant product ion from a nucleotide analog by using ion-pairing LC-MS/MS with positive-ion mode. Cai et al [2] reported the selection of most abundant MS/MS quantitative ions of 6 ribo-and ribodeoxynucleotides by using ion-pairing LC coupled with positiveion ESI-MS/MS.…”
mentioning
confidence: 99%